Revealing the diagnosis of children with special health needs: perceptions of parents (Research, Society and Development, 2020)
The objective is to identify the parents' perception about disclosing the diagnosis of children who need special health care. Qualitative study carried out with seven parents of children who need special health care, whose data were produced through a semi-structured interview with thematic content analysis. Three categories were identified: 1) feeling of the parents when the diagnosis of the child needing special health care was revealed, in which they expressed feelings of bewilderment, astonishment, shock, denial, guilt, sadness, among others; 2) parents' perception of how the diagnosis was revealed, in which they pointed out, the way in which the diagnosis was revealed; and 3) parents' perception of the change in routine after disclosure of the diagnosis. They said that everything changed, requiring greater availability of time and dedication to care for the child. Thus, health professionals, when disclosing the diagnosis, need to provide it in an interprofessional manner and in an appropriate place, in addition to promoting emotional support, facilitating acceptance, and minimizing negative feelings.